2021
DOI: 10.1007/s40801-021-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns in Patients with Locally Advanced or Metastatic Non-Small-Cell Lung Cancer Treated with Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors: Analysis of US Insurance Claims Databases

Abstract: Background Most patients with epidermal growth factor receptor mutation-positive (EGFRm) non-small-cell lung cancer (NSCLC) acquire resistance to first-line (1L) first-or second-generation (1G/2G) EGFR-TKIs; therefore, it is important to optimize 1L treatment to improve patient outcomes. Objective To retrospectively examine treatment patterns in locally advanced/metastatic NSCLC using MarketScan ® Commercial and Medicare Supplemental Databases (all US census regions). Patients and methods Adults with a lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…This retrospective study using real‐world US claims data investigated a total of 2505 mNSCLC patients newly initiating 1L EGFR TKIs and described key patient characteristics and treatment patterns. Median ages of patients were similar across all three cohorts and the patients were predominantly female, which is consistent with the populations reported in other real‐world studies for 1L EGFR TKI use 11–13 and with the prevalence of EGFR mutations in women 22 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This retrospective study using real‐world US claims data investigated a total of 2505 mNSCLC patients newly initiating 1L EGFR TKIs and described key patient characteristics and treatment patterns. Median ages of patients were similar across all three cohorts and the patients were predominantly female, which is consistent with the populations reported in other real‐world studies for 1L EGFR TKI use 11–13 and with the prevalence of EGFR mutations in women 22 …”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the results of this real‐world study demonstrated a longer median 1L treatment duration with osimertinib (17.8 months) as compared with earlier generation EGFR TKIs (8.7 months for first‐generation and 10.5 months for second‐generation EGFR TKI) in the real‐world setting. Other retrospective database studies conducted using US claims data have reported similar median 1L treatment durations for first‐ and second‐generation EGFR TKIs, including 7.7–8.2 months for a combined cohort of EGFR TKIs 13 and 9.9 months for erlotinib and 12.1 months for afatinib 12 . Furthermore, time to treatment discontinuation has previously been shown to be a proxy for PFS 23 and we indeed found that the median durations of first‐ and second‐generation EGFR TKI treatments in this study were comparable to the median PFS reported in their respective clinical trials (9.7–13.3 months 3,24,25 for erlotinib and 11.0–11.1 months 26–28 for afatinib), as well as the median PFS for first‐generation EGFR TKIs reported in the phase III FLAURA trial (10.2 months) 29 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…At disease relapse, almost a quarter of patients received only locoregional treatment and all EGFR -mutant patients received an EGFR-TKI ( 20 , 21 ), as described in previous similar series of EGFR mutant NSCLC, eventually followed by a variety of combination therapies ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main primary types of lung cancer is non-small-cell lung carcinoma (NSCLC), which is characterized by poor prognosis and long asymptomatic [1][2][3][4]. Some genes that encode signaling proteins that are crucial for cellular proliferation and survival, such as epidermal growth factor receptor (EGFR) gene, had found to have many different mutations in tumor tissue, and these mutations are related to selection of appropriate therapy [5][6][7][8][9]. Some new therapeutic agents, such as the epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) ge tinib and erlotinib, can produce a response for only NSCLCs carrying an EGFR mutation [10,11].…”
Section: Introductionmentioning
confidence: 99%